The Rationality of Household Consumption in Konda District - Sari, Kiki Novita (Robust: Research of Business and Economics Studies, 2025)
The background of this research is based on limited economic growth in rural areas, which often limits population access to a variety of consumption choices. Factors such as accessibility, local preferences, and limited financial resources can influence how households prioritize their spending. Therefore, this research aims to provide in-depth insight into the dynamics of consumption in Wonua Village. The main objective of this research is to analyze household consumption patterns and explore the factors that influence consumption decisions in Wonua Village. And to find out the level of rationality of household consumption in Wonua village from an Islamic economic perspective. The method used in this research is qualitative research using qualitative descriptive methods with data collection using interviews and research questionnaires. The research results show that household consumption patterns in Wonua village, sub-district. Konda is used for food and non-food consumption expenditure, and household consumption expenditure is adjusted to income and the number of families living in it. The rationality of household consumption from an Islamic Economics perspective is in the medium category because the Mean value is 39.16. This value is in the medium category with a value interval of 33 ≤ X ≤ 45. Keywords: Rationality, Household Consumption, Islamic Economic Perspective